Strategi Negosiasi Komunikatif dalam Talk Show Digital: Analisis Retorika pada Program Mata Najwa - Akmal Syah; Suryani Musi; Risdayanti. J; Nur Alwadina; Nurul Azizah Sutedjo (MAN 4 Kota Pekanbaru, 2026)
This study examines communicative negotiation strategies in digital talk shows through a rhetorical communication analysis of the Mata Najwa program. In the context of contemporary digital public communication, talk shows function not only as platforms for information dissemination but also as spaces for negotiating opinions, managing public discourse, and constructing communicative legitimacy. This research aims to analyze communicative negotiation strategies, persuasive rhetoric, and communication deadlock management in digital public dialogue. The study employed a qualitative descriptive approach using rhetorical communication analysis on three of the most viewed episodes of Mata Najwa on YouTube, namely Eksklusif: Prabowo Subianto Bicara, 20 Tahun Timor Leste: Cerita Setelah Merdeka, and Ujian Reformasi: Perlawanan Mahasiswa (Part 1). Data were collected through digital content observation, documentation, and dialogue transcription, then analyzed using the Miles and Huberman interactive analysis model. The findings indicate that communicative negotiation in the program is reflected through issue reframing, argumentative clarification, emotional management, adaptive communication strategies, and rhetorical approaches to overcoming communication deadlocks. Furthermore, persuasive rhetoric in the program is constructed through the integration of ethos, pathos, and logos in building public credibility, emotional engagement, and argumentative legitimacy. The study concludes that the success of digital public communication is influenced not only by the ability to deliver information but also by communicative negotiation skills, rhetorical persuasion, and adaptive communication management in dynamic public discourse. This study contributes to the development of digital communication and public relations studies, particularly regarding rhetorical negotiation practices in contemporary digital talk shows.